Regulatory T cell subsets in bullous pemphigoid and dipeptidyl peptidase-4 inhibitor-associated bullous pemphigoid. Issue 1 (October 2020) - Muramatsu, Ken; Zheng, Miao; Yoshimoto, Norihiro; Ito, Takamasa; Ujiie, Inkin; Iwata, Hiroaki; Shimizu, Hiroshi; Ujiie, Hideyuki
Highlights: Treg cells were increased in conventional BP patients before treatment. Treg cells were not increased in dipeptidyl peptidase-4 inhibitor-associated BP. Effector Treg cells positively correlated with disease severity in conventional BP. Abstract: Background: Regulatory T (Treg) cells play an essential role in peripheral immune tolerance. Bullous pemphigoid (BP) is the most common blistering disease and is caused by autoantibodies to two BP antigens: type XVII collagen and BP230. Recently, we reported that Treg cell dysfunction may cause the production of autoantibodies to BP antigens. Several studies have suggested an association between Treg cells and BP pathogenesis. However, Treg cells are heterogeneous in humans, leading to inconsistent results in previous studies. Objective: To assess functional Treg subsets in BP. Methods: We examined three distinct Treg subsets in conventional BP (cBP) patients before versus after systemic corticosteroid treatment, dipeptidyl peptidase-4 inhibitor-associated BP (DPP-4i-BP) patients, younger controls and older controls. Results: We found that total Treg cells and all Treg cell subsets were increased in cBP patients before treatment and decreased by systemic corticosteroid treatment. In contrast, neither total Treg cells nor all Treg subsets were increased in DPP-4i-BP. Notably, CD45RA − Foxp3 hi effector Treg cells positively correlated with disease severity in cBP, whereas CD45RA + Foxp3 lo naïve Treg cells positively correlated with the disease severity in DPP-4i-BP. Conclusion: These findings suggest that Treg cells are differently involved in the pathogeneses of cBP and DPP-4i-BP.